Transfer of IGF2BP3 Through Ara-C-Induced Apoptotic Bodies Promotes Survival of Recipient Cells - Gou, Junjie; Li, Hongjiao; Bi, Jingjing; Pang, Xingchen; Li, Xiang; Wang, Yi (Frontiers in Oncology, 2022)
Cytosine arabinoside (Ara-C) has been the standard therapeutic agent for myelodysplastic syndromes (MDS) and adult acute myeloid leukemia (AML) patients for decades. Considerable progress has been made in development of new treatments for MDS/AML patients, but drug resistance remains a major clinical problem. Apoptotic bodies (ABs), produced by late apoptotic cells, can enclose bioactive components that affect cell-cell interactions and disease progression. We isolated and identified drug-induced ABs from Ara-C-tolerance cells. Treatment of sensitive cells with Ara-C-induced ABs resulted in Ara-C-resistant phenotype. We further investigated components and functions of Ara-C-induced ABs. Proteomics analysis in combination with mass spectrometry revealed that Ara-C-induced ABs carried numerous RNA-binding proteins, notably including insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3). Delivery of AB-encapsulated IGF2BP3 promoted survival of recipient cells by activating PI3K-AKT and p42-44 MAPK pathways. High IGF2BP3 level in ABs from MDS/AML patient plasma was correlated with poor overall survival. Our findings demonstrate that AB-derived IGF2BP3 plays an essential role in acquired Ara-C resistance in MDS/AML patients, and is a potential therapeutic target for suppression of Ara-C resistance.